Investigation of primary school students solving arithmetic verbal problems - Bal, Ayten Pınar; Dinç Artut, Perihan (Intelektual Pustaka Media Utama, 2022)
The study determined the arithmetic verbal problem solving skills of primary school students and to examine them according to grade level and mathematics achievement variables. The study was designed according to the relational survey model, one of the quantitative research methods. The population of the research consists of students studying in public primary schools in the central districts of a large city in the south of Turkey. The sample consisted of 1,865 students determined according to the disproportionate stratified sampling method. The